Saliva-based point-of-care assay to measure the concentration of pyrazinamide using a mobile UV spectrophotometer - Chen, Ricky Hao; Nguyen, Thi Anh; Kim, Hannah Yejin; Stocker, Sophie L; Alffenaar, Jan-Willem C (Journal of antimicrobial chemotherapy, 2025)
Pyrazinamide, one of the first-line antituberculosis drugs, displays variability in drug exposure that is associated with treatment response. A simple, low-cost assay may be helpful to optimize treatment. This study aimed to develop and validate a point-of-care assay to quantify the concentration of pyrazinamide in saliva. All measurements were conducted using the nano-volume drop function on the mobile ultraviolet (UV) spectrophotometer (NP80, Implen, Germany). Assay development involved applying second derivative spectroscopy in combination with the Savitzky-Golay filter between wavelengths of 200-300 nm to increase spectral resolution. Assay validation included assessing selectivity, linearity, accuracy, precision, carry-over and matrix effects. Specificity was also analysed by evaluating the impact of co-administered medications on pyrazinamide results. Sample stability was measured at various temperatures up to 40°C. The calibration curve (7.5-200 mg/L) was linear (R2 = 0.9991). The overall accuracy (bias%) and precision (CV%) ranged from -0.66% to 5.15%, and 0.56% to 4.95%, respectively. Carry-over and matrix effects were both acceptable with a bias% of <±4% and CV% of <7.5%. Commonly co-administered medications displayed negligible interferences. Levofloxacin displayed analytical interference (bias% = -10.21%) at pyrazinamide concentrations < 25 mg/L, but this will have little clinical implications. Pyrazinamide was considered stable in saliva after 7 days in all storage conditions with a CV% of <6.5% and bias% of <±10.5% for both low- and high-quality control concentrations. A saliva-based assay for pyrazinamide has been successfully developed and validated using the mobile UV spectrophotometer.